The akar kucing (Acalypha indica l.) Leaves extract cream 4% prevented the formed melanin cell of guinea pigs (Cavia porcellus) skin that exposed to ultraviolet B - Aditia Martanti; Wayan Weta; Aagp Wiraguna (Fakultas Kedokteran Universitas Udayana, 2021)
Background: Hyperpigmentation is caused by an increase in the amount of melanin in the epidermal skin layer. The natural topical ingredients possibly has a role protect and reduce damaged caused by exposure to ultraviolet rays, with minimal side effects. The active compounds in akar kucing leaves are flavonoids, tannins and phenols. The aim of the study is to prove the administration of akar kucing (Acalypha indica L.) leaves extract 4% can prevented the formed of melanin cell in guinea pig skin (Cavia porcellus) that exposed to UVB. Methods: The randomized post-test only control group design, was conducted with 36 male guinea pigs (Cavia porcellus), local strains, aged 3 months, weighing 300-350mg. Both group was exposed to UVB for 5 minutes with dose 65 mJ/cm2, six times for 2 weeks. The control group was given basic cream. The treatment group was given akar kucing (Acalypha indica L.) leaves extract 4% cream. After two weeks intervention, punch biopsied tissue of guinea skin performed to subcutaneous then it was stained with Masson-Fontana. Finally melanin cell was counted compared to epidermic area in percentage unit. Results: All samples of guinea pigs were successful until they were fit for post-test. The melanin cell in the treatment group with 1.65 ± 0.495% was lower than melanin cell in the control group 18.5 ± 1.18, significantly (p <0,001). Conclusion: Cream of akar kucing (Acalypha indica L.) leaves extract 4% prevented the formed of melanin cell of the skin of guinea pig (Cavia porcellus) that exposed to UVB.